(untitled) (Encuentros, 2024)
In Latin America and the Caribbean, policymakers rarely take Afro-descendant cosmovisions seriously in the design of urban public policies and territorial development. After reviewing the literature on the emerging concept of “urban extractivism”, which implies extreme environmental exploitation, state neglect, illegal territorial domination, socio-economic and racial segregation, we review studies of recent struggles and actions of re-existence that some Afro-descendant communities are taking to influence their daily lives. Focusing on specific contexts in Colombia and Brazil, we find that some of these communities’ practices mean that an Afro-descendant perspective should be included in the development policy and local planning, as new forms of Right to the City.